NITRATE EXPOSURE IN DRINKING WATER AND CANCER RISK: LITERATURE REVIEW - Mutia Ardhaneswari; Bambang Wispriyono (Jurnal Kesehatan Tambusai, 2021)
Background: Nitrate is a contaminant in water sources and it can be found in surface water and groundwater. Nitrate enter the body through consumption of water and food that contain nitrate. Nitrate may cause cancer, because there are still few studies that report the relationship between nitrate and the risk of cancer. This study aims to review the relationship between the nitrate exposure and risk of various types of cancer based on the results of previous studies. Subject and Method: the method is literature review with a database of PUB MED and SCOPUS, using a systematic search strategy and in accordance with the criteria determined at the start of the study. The article used is a research article with information related to nitrate exposure from drinking water sources and its health effects, namely cancer, published in 2010-2020. Results: A total of 96 literatures are searched from database, 9 studies that met the inclusion criteria were selected for analysis. The selected studies used case control study design (3 articles) and cohort (6 articles). Conclusion: Most studies report that there are positive association between nitrate consumption in drinking water and the risk of developing colorectal, bladder, kidney, gastrointestinal, ovarian and thyroid cancer.